How Effective is Mathematical Self-Efficacy Influencing Interpersonal Intelligence of Elementary School Students - Yuliyanto, Aan; Yulianto, Ade (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
The benefits of mathematical self-efficacy as a driver of students in facing their challenges in learning mathematics, and students' interpersonal intelligence as the ability of students to interact with people around them in learning. This research was inspired to provide an understanding of the relationship between mathematical self-efficacy and students' interpersonal intelligence. The research applied the correlational method. Participants as a sample in the study were 27 first-grade elementary school students in Purwakarta. Instruments in measuring mathematical self-efficacy used questionnaires and interpersonal intelligence was measured by observation. The findings of this research inform us that there is no significant relationship between students' mathematical self-efficacy and the interpersonal intelligence of elementary school students. Furthermore, mathematical self-efficacy had a very limited influence on students' interpersonal intelligence. Thus, an increase or decrease in mathematical self-efficacy cannot be guaranteed to also occur in the interpersonal intelligence of elementary school students